PENGARUH STRUKTUR MODAL TERHADAP PPh BADAN TERUTANG PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI SEMEN YANG TERDAFTAR DI BEI PERIODE 2010-2013 - Simamora, Patar; Ryadi, Muhamad Ressa Mahardika (Universitas Pakuan, 2015)
The One of the companys goal is to maximize the welfare of shareholders or investors by maximizing the companys value by obtaining the maximum profit the other hand, paying taxes is one of the companys liabilities that canât be avoided. However, the company can undertake tax management so that the amount of tax to be paid to be low. One tax management relating to the use of debt is the interest expenses on debt including the cost of business that can be a deduction from income, causing the companys taxable income is reduced, which in turn will reduce the amount of tax to be paid by the company. Data processing method is by descriptive statistical analysis with analysis tools that multiple linear regression. The results showed that the value of the variable LDAR is that t hitung> t tabel or 2,384> 2,229 then H0 rejected, which means LDAR partially affect the corporate income tax payable. For the value of the variable DER is t hitung> t tabel or 2,350> 2,229 then H0 rejected, which means DER partially affect the corporate income tax payable. Simultaneous testing values obtained F count> F table or 6.931> 2.816 means LDAR and DER simultaneously have an impact on corporate income tax payable. It can be concluded that: (1) LDAR affect the corporate income tax payable, (2) DER affect the corporate income tax payable, and (3) LDAR and DER jointly affect the corporate income tax payable.Â Key words: LDAR, DER, and Income Tax Payable